2007
DOI: 10.1152/ajpcell.00583.2006
|View full text |Cite
|
Sign up to set email alerts
|

Slc7a7 disruption causes fetal growth retardation by downregulating Igf1 in the mouse model of lysinuric protein intolerance

Abstract: The solute carrier family 7A member 7 gene (SLC7A7) encodes the light chain of the heterodimeric carrier responsible for cationic amino acid (CAA) transport across the basolateral membranes of epithelial cells in intestine and kidney. Mutations affecting SLC7A7 cause lysinuric protein intolerance (LPI), a multiorgan disorder with clinical symptoms that include visceromegaly, growth retardation, osteoporosis, hyperammonemia, and hyperdibasicaminoaciduria. Here, we describe the consequences of inactivating Slc7a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 31 publications
(26 reference statements)
4
28
1
Order By: Relevance
“…The significance of the neutral amino acid transporter LAT2 in the placental function is still unclear since the homozygous Lat2 gene knockout mice show no apparent phenotypes associated with the defects of placental function (45). In contrast, the knockout of y ϩ LAT1, a transporter for both cationic and neutral amino acids, causes IUGR and highly frequent neonatal lethality (16 of 18 neonates died within 24 h after birth) (46). Although the localization of LAT2 and y ϩ LAT1 in the developing placental tissues has not been investigated in detail, the severe impairment of syncytiotrophoblast formation shown in the present study suggests that at least these other light chains of 4F2hc do not substitute for LAT1 in the placental development in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of the neutral amino acid transporter LAT2 in the placental function is still unclear since the homozygous Lat2 gene knockout mice show no apparent phenotypes associated with the defects of placental function (45). In contrast, the knockout of y ϩ LAT1, a transporter for both cationic and neutral amino acids, causes IUGR and highly frequent neonatal lethality (16 of 18 neonates died within 24 h after birth) (46). Although the localization of LAT2 and y ϩ LAT1 in the developing placental tissues has not been investigated in detail, the severe impairment of syncytiotrophoblast formation shown in the present study suggests that at least these other light chains of 4F2hc do not substitute for LAT1 in the placental development in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The neutral and dibasic AA exchanger (antiporter) b transporter responsible for cystine reabsorption in the kidney, but transports cationic as well as neutral AAs across the luminal enterocyte membrane (Bertran et al, 1992;Palacin et al, 1998Palacin et al, , 2005Feliubadalo et al, 1999;Pfeiffer et al, 1999;Dave et al, 2004). Among the basolateral enterocyte transporters, the AA exchangers y 1 LAT1-4F2hc and LAT2-4F2hc (SLC7A8-SLC3A2) (Pfeiffer et al, 1999;Rossier et al, 1999;Sperandeo et al, 2007) and the aromatic AA uniporter TAT1 (SLC16A10) (Kim et al, 2001;Quinones et al, 2004;Ramadan et al, 2006Ramadan et al, , 2007Mariotta et al, 2012) were shown to promote accumulation or efflux of AA from the enterocytes to the extracellular space. In addition, the functional interaction between different transporters can affect the net flux of AAs (Nguyen et al, 2007;Ramadan et al, 2007;Verrey et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Sperandeo et al (Sperandeo et al 2007) reported on the generation of a slc7a7 À/À mice that experienced intrauterine growth restriction (IUGR) by downregulating IGF-1 expression in fetal liver.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies on slc7a7 À/À mice exclude CAA depletion as a primary cause of IUGR (Sperandeo et al 2007), it is not possible to exclude its role in postnatal growth delay. In fact, it is well known that GH secretion can be promoted by intravenous administration of various AA, and the stimulatory effect of some AA on GH is clinically used as a method to assess the responsiveness of the GH secretory system.…”
Section: Discussionmentioning
confidence: 99%